(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
The linguistic aspects of cultural identity, i. e. the question of understanding the different language of The Other, is widely embraced in Hungarian literature in Vojvodina; Hungarian literature of the region is addressed by numerous reflections that point to linguistic distinction, as well as the existence of regional standard language and its legitimacy. Alongside with this, the illusion of multicultural identity also emerges as well as the theme of its social-historical failure. Teaching Hungarian literature in Vojvodina also deals with these linguistic and language-usage topics.